Developing G-Smartive (Getting Smart in Narrative) Multimedia as an Aid to Learn Reading of Narrative Text for Tenth Graders of Vocational High School - Putri Ika Ayundha Ningtyas (EDUCAFL : Journal of Education of English as Foreign Language, 2020)
This study aims to develop the appropriate learning multimedia named G-Smartive (Getting Smart in Narrative) that provides the interesting components, learning materials, and applies game-based learning. It uses as aid to learn reading especially narrative text for tenth graders of Vocational High School. The method of this study was developmental research model purposed by Borg & Gall (2003). The steps were need analysis, product development, expert validation, first revision, product try-out, final revision, and final product. The participant of this study was X KJB students in SMK PGRI 3 Malang. The instruments used were need analysis questionnaire, validation sheet, and questionnaire for product try-out. The data was analysed quantitatively. Regarding the result of need analysis and document analysis, G-Smartive presented three main materials which were reading comprehension, language feature, and vocabulary category. The result of validation showed that G-Smartive was suitable and appropriate to use for tenth grade students, but it needed some revisions. The research finding showed that all the aspects were in good category. The product also got the positive response from the students. G-Smartive gave contributions in supporting language learning, increasing the students’ language proficiency, and making the process of acquisition easier, and more interesting.